Being Minority in Papua: Religious and Political Identity Struggle of the Dani Muslims - Ade Yamin; Irwan Abdullah; Achmad Nurmandi; Hasse Jubba; Zuli Qodir (Graduate Program of Pontianak Institute of Islamic Studies, 2019)
The issue of religious and political identity of the Dani Muslims in Papua has been associated to social construction of the ethnic and religious aspects as the basis of political policies by the local government. The local government present in the form of Undang-Undang Otonomi Khusus Papua (UU OTSUS Papua) or the Law Number 21 of 2001 concerning Special Autonomy for Papua has been understood to become one of the keys playing roles in constructing the identity of people in modern Papua. This work attempts to review the process of becoming minority of the Dani Muslims within the context of the Papua society. They live in the central mountains with limited infrastructure and access to modern life. The work suggests that the Dani Muslim has become minority in terms of political representation as well as religious identity due to three conditions. First, the practice and implementation of the Law Number 21 of 2001 concerning Special Autonomy for Papua has significantly influenced the live of the Dani Muslims with regards to their political representation as well as religious identity. Second, they embrace Islam as a way of life and have to deal with the cultural conditions of the Dani community in general that are very consistent in maintaining their local tradition. Third, the domination of religious symbols used in public spaces has been found to have much influence to the identity of minority groups. The Christian Papuans later made further claims of Papua as the Land of Christ has had a broad impact not only on the access to public services for the Dani Muslims but has also presented them with new pressure and marginalized in terms of political position and religious group existence.